An Analysis of the Role of the Balanced Scorecard on Firm Performance: A Study in the Banking Sector of Ho Chi Minh City - Nhung, Vu Cam (Journal of Ecohumanism, 2025)
This study aims to assess the impact of Balanced Scorecard on the performance of banks operating in the banking sector of Ho Chi Minh City based in four fundamental perspectives of BSC: financial, customer, internal business processes, and learning and growth. In addition, under the conditions of this dynamically changing economic environment, Balanced Scorecard has a very positive influence on the performance of the banks. The study adopted a process of convenient sampling, collecting data from banking sector employees and managers, totaling 283. An attempt has been made in this research to establish, with exactitude, the relationship between dimensions of BSC and Smart PLS software, which helps provide a thorough analysis of the data in determining the effects of the dimensions of BSC on organizational performance. From an in-depth study, it is shown that the four basic BSC perspectives: financial, customer, internal business processes, learning and growth have a positive effect on banks’ overall performance in this vibrant economic context. Results imply that managers in the banking sector can use the Balanced Scorecard to identify strategic objectives by aligning them with operational action that allows a more balanced approach to growth. Furthermore, the research emphasizes that such strategic alignment fosters balanced organizational growth and supports long-term stability. This study makes a valuable contribution to the limited body of research on the application of BSC in Vietnam’s banking sector, particularly in Ho Chi Minh City, by proposing a model that other industries in emerging markets can adopt to improve performance.